Optimizing of gross pollutant trap to improve the maintenance at Sungai Bunus Malaysia - Munir S.N.U.; Sidek L.M.; Haron S.H.; Said N.F.M.; Basri H.; Ahmad R.; Dom N.M.; Ismail M.A. (American Institute of Physics Inc., 2023)
This paper discusses the efficiency of installed Gross Pollutant Traps (GPTs) for optimizing to improve the maintenance at Sungai Bunus, Malaysia. An increasing population due to urbanization contributes to the generation of increased amounts of rubbish and waste material. The uncontrolled dumping of debris can exert a significant impact on aesthetics and river water quality, both of which affect the quality of life in urban environments and increased management costs. The performance of GPTs is strongly dependent upon the specific site criteria including type of land use, hydrological regime and maintenance frequency. The study is conducted by providing a management and planning tool for maintenance purposes of the gross pollutants in the urban areas under one of the sub-catchment in River of Life (ROL) project, namely Sungai Bunus, Malaysia. The gross pollutant wet load data was collected and analysed based on maintenance data from January 2015 to December 2016 for a total number of 55 proprietary GPTs. The data collected from gross pollutant wet load was found to be trapped inside the GPTs from different types of land use which is residential, commercial and mixed development. Apart from that, simple calculation on the optimum number is calculated by comparing with other countries which are Spring and Capetown, South Africa and Australia. The result shows the reduction 47.21% of the average wet load from the year 2015 to 2016. The contribution from each type of land use shows 51.37% of the source of gross pollutants in Sg Bunus, Malaysia comes from residential area followed by mixed development and commercial area with the percentage contribution of 37.17% and 11.46% respectively. The optimum numbers of gross pollutant trap need to be added based on comparing with other countries was Spring South Africa (55 GPTs), Cape Town South Africa (194 GPTs) and Australia (199 GPTs). From the results, the frequency maintenance was every two month for Sungai Bunus Malaysia. 2018 Author(s).